34/#806 Patterns of palliative care utilization by women with gynecologic malignancies in Ontario, Canada: a 13-year population-based retrospective analysis. (4th December 2022) - Mah, Sarah J; Eiriksson, Lua; Ramirez, Daniel Carter; Schnarr, Kara; Seow, Hsien
Abstract : Objectives: Early palliative care (PC) (≥6–12mo from death) has been associated with improved patient quality-of-life, less aggressive end-of-life care, and prolonged survival, and is understudied in gynecology. We characterized patterns of PC utilization and predictive factors in gynecologic cancer patients. Methods: We conducted a population-based, retrospective cohort study of gynecologic cancer decedents in Ontario from 2006–2018 using ICES-linked administrative healthcare data. Multivariable logistic regression was used to determine factors associated with PC utilization. Results: In this cohort of 16, 237 women, 93.4% of decedents accessed palliative care, initially in the outpatient setting for 68.8% and institutionally for 31.2%. Palliative care was initiated a median 127 days before death (IQR 38–361d), and PC users accessed a median 8 institutional days (IQR 0–21d) and 41 community days (IRQ 3–174d). While use of community PC gradually increased toward the end of life, use of institutional palliative care exponentially increased from 12 weeks until death. On multivariable analyses, factors significantly associated with an increased likelihood of receiving palliative care were longer cancer-related survival and Deyo-Charlson comorbidity score ≥1. Factors significantly associated with decreased likelihood of palliative care were age ≥80 years, diagnosis of uterine or vulvar-vaginal cancers, initial diagnosis of stage I-III malignancy (vs. stage IV), living rurally or in the third income quintile, or death after 2007. Conclusions: While >90% of gynecologic cancer decedents accessed palliative care, median initiation was within the last 4 months of life (late PC), which may result in suboptimal quality of disease and end-of-life care. Access to PC may be inequitable.